Biochar, wood ash and humic substances mitigating trace elements stress in contaminated sandy loam soil: Evidence from an integrative approach. (July 2018) - Pukalchik, Mariia; Mercl, Filip; Terekhova, Vera; Tlustoš, Pavel
Abstract: We conducted a pot experiment with biochar (BC), wood ash (WA), and humic substances (HS) to investigate their effect on As, Zn, Cu, Cd and Pb mobility in soil, as well as enzyme activities involved in C-, N-, and P-cycles, and Eisenia foetida toxicity in multi-contaminated soils. Amendments were dosed to increaseеру soil pH from initial 6.0 to ∼6.5 and ∼7.0. Applying amendments has revealed, that WA significantly immobilized Cu, Zn and Pb, BC – Cu and Zn, and HS decreased solely Cu mobility in soil. The partition indices of Zn, Cu, and Pb, quantitatively describing the bioavailable species of elements in soil, were the lowest for WA. Changes in the water-soluble species of metals were more pronounced than in the exchangeable ones for all amendments. An opposite effect was observed on enzyme activity and earthworm toxicity for the WA and carbonaceous amendments. The BC and HS provided favourable soil conditions to dehydrogenase, β-glucosidase, urease activity and fluorescein diacetate hydrolysis, while WA significantly decreased the activity of all the mentioned enzymes in soil. The results are supported by an enzymes-based weighted mean index, being the highest for BC and HS and the lowest for WA (lower than in the control sample). At the same time, WA was suitable to eliminate the trace elements' stress to earthworms (biomass endpoints and cocoons production). Our data revealed that each amendment has its own advantages and disadvantages. The choice of the most suitable amendment therefore should always be made within an integral approach and based on the purpose of remediation. Graphical abstract: Highlights: Wood ash is reliable to decrease the water- and weak acid-extractable Cu, Zn, and Pb soil content. Carbonaceous amendments decrease weak acid-extractable Cu, and Zn soil content. Wood ash depressed soil enzymes activity. Biochar addition may pose a risk to Eisenia foetida survival. Minor addition of humic substances creates favourable soil condition for enzymes and earthworms.